Design, synthesis and application of luminescent metal tetrazolato complexes in optical imaging - Werrett, Melissa Vivienne (Curtin University, 2014)
Fundamental investigation into a series of Re(I) tetrazolato complexes as optical imaging agents provided insight into how structural modifications influence their chemical, photophysical and biological properties. Modulation of the complexes through protonation and methylation of the tetrazolato ligand led to improved photophysical performance. Functionalisation at the diimine ligand revealed photophysical output is not appreciably altered. Live cell imaging with the Re(I) complexes showed HeLa cell uptake with perinuclear localisation.